Tumor microenvironment-responsive engineered hybrid nanomedicine for photodynamic-immunotherapy via multi-pronged amplification of reactive oxygen species - Jinglin Zou; Cong Jiang; Qiangsheng Hu; Xinlin Jia; Shuqi Wang; Shiyue Wan; Yuanqing Mao; Dapeng Zhang; Peng Zhang; Bin Dai; Yongsheng Li (Nature Communications)
Abstract Reactive oxygen species (ROS) is promising in cancer therapy by accelerating tumor cell death, whose therapeutic efficacy, however, is greatly limited by the hypoxia in the tumor microenvironment (TME) and the antioxidant defense. Amplification of oxidative stress has been successfully employed for tumor therapy, but the interactions between cancer cells and the other factors of TME usually lead to inadequate tumor treatments. To tackle this issue, we develop a pH/redox dual-responsive nanomedicine based on the remodeling of cancer-associated fibroblasts (CAFs) for multi-pronged amplification of ROS (ZnPP@FQOS). It is demonstrated that ROS generated by ZnPP@FQOS is endogenously/exogenously multiply amplified owing to the CAFs remodeling and down-regulation of anti-oxidative stress in cancer cells, ultimately achieving the efficient photodynamic therapy in a female tumor-bearing mouse model. More importantly, ZnPP@FQOS is verified to enable the stimulation of enhanced immune responses and systemic immunity. This strategy remarkably potentiates the efficacy of photodynamic-immunotherapy, thus providing a promising enlightenment for tumor therapy.